1993
DOI: 10.1017/s0022112093002721
|View full text |Cite
|
Sign up to set email alerts
|

A critical-layer analysis of the resonant triad in boundary-layer transition: nonlinear interactions

Abstract: A systematic theory is developed to study the nonlinear spatial evolution of the resonant triad in Blasius boundary layers. This triad consists of a plane wave at the fundamental frequency and a pair of symmetrical, oblique waves at the subharmonic frequency. A low-frequency asymptotic scaling leads to a distinct critical layer wherein nonlinearity first becomes important, and the critical layer's nonlinear, viscous dynamics determine the development of the triad.The plane wave initially causes double-exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 19 publications
4
69
0
Order By: Relevance
“…At a fully nonlinear stage of development the disturbances exhibited rapid explosive growth, which was, again, qualitatively similar to that found by other theoretical approaches (see Spalart & Yang 1987;Zelman & Maslennikova 1993). Approximately the same theoretical approach as that of Goldstein & Lee (1992) was applied by Mankbadi et al (1993) to the Blasius boundary layer. In addition, they took into account viscous effects and the self-interaction of three-dimensional subharmonic waves.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…At a fully nonlinear stage of development the disturbances exhibited rapid explosive growth, which was, again, qualitatively similar to that found by other theoretical approaches (see Spalart & Yang 1987;Zelman & Maslennikova 1993). Approximately the same theoretical approach as that of Goldstein & Lee (1992) was applied by Mankbadi et al (1993) to the Blasius boundary layer. In addition, they took into account viscous effects and the self-interaction of three-dimensional subharmonic waves.…”
supporting
confidence: 82%
“…For nonlinear stages of boundary-layer transition, the first theories of resonant interactions of TS waves were developed by Maseev (1968) and Craik (1971) and later by Herbert (1975), Volodin & Zelman (1978), Smith & Stewart (1987), Goldstein & Lee (1992), Mankbadi, Wu & Lee (1993) and Wu (1995) and in a great number of other subsequent studies; for a review see Borodulin, Kachanov & Koptsev (2002b), for example. The classical Craik's triad consists of a two-dimensional (2D) primary (fundamental) instability wave, with frequency f 1 , having relatively large amplitude and two weak oblique subharmonic waves, with frequency f s = f 1 /2, propagating at angles to the mean flow direction with the same values but opposite signs.…”
Section: Introductionmentioning
confidence: 99%
“…At high Reynolds number, the transition process becomes 3D (see for instance, Ref. [25]). However, at low-to-moderate Reynolds numbers, for which the current results are conducted, experimental and computational results in Ref.…”
Section: Aeroacoustics Volume 14 • Number 3 and 4 • 2015mentioning
confidence: 99%
“…Unfortunately, they assumed that the critical layer was passive. A correct asymptotic theory for resonanttriad of T-S waves was given by Mankbadi et al [29] and Wu [3~ who showed that contrary to what was assumed in Ref. [28], the critical layer is in fact the most active region, contributing the dominant nonlinear term.…”
Section: Ato(xl) = ~Oaomentioning
confidence: 99%